Acquired pneumonia in the community lethality and their relationship with the stratification process, the fulfillment of suggestions about intrahospitalary location and the antimicrobial initial treatment (European Journal of Health Research, 2021)
Community-acquired pneumonia continues being an important cause of morbimortality at world level. The objective was determining the relationship between community-acquired pneumonia mortality and the frequency and quality of the stratification process, and all of this with the fulfillment of the stratification instrument’s suggestions as for both the patient's intrahospitalary location and the initial antimicrobial treatment. It was carried out an observational study with a descriptive correlational design on a population of 1,809 patients hospitalized between the years 2009 and 2019. Mortality was evaluated according to different study variables. The statistical analysis was based on odds ratio, with a significance level of 95%. Global mortality of the series was of 28%, with the highest value on patients with serious pneumonia and scarce recovery probabilities (OR 9, 5 [7;12,8]). It was proven a significant association between the non-stratification and the lethality (OR 1,6[1,2;2,2]), and between the incorrect stratification and the mortality (OR 1,4[1,07;1,8]). Patients with intrahospitalary location different to the stratification instrument’s suggestion showed a higher mortality (OR 2,2[1,3;3,6]). Only in patients with moderate pneumonia and high probabilities of non-satisfactory evolution a higher lethality was observed in the sick persons that received antimicrobial therapeutic different from the one suggested in the stratification instrument (OR 1, 7[1,3; 2, 2]). As conclusions, it was proven a narrow relationship between the non-stratification, the incorrect stratification or the intrahospitalary location of the sick person different from the suggestion of the stratification instrument, and the mortality for community-acquired pneumonia.
Keywords: community-acquired infections; pneumonia; hospital admission; mortality